Terminologija v Evropski uniji - Fajfar, Tanja (Lingua Slovenica, 2017)
The monograph ('On Terminology in the European Union') focuses on the creation of the Slovene version of the terminology of the EU. The primary task of the terminology is to ensure effective communication. Therefore, it should be unambiguous and consistent. Multilingualism is a fundamental principle of the language regime of the EU and it is achieved through translation. Translation is also one of the most common naming procedures when creating EU terminology. Before creation of the new term it is very important to identify the content of the concept for which lawyers are certainly most qualified. The judgments of the Court of Justice of the EU are translated by lawyer-linguists, who are legal professionals with law degree in their main language. They are employed in all EU institutions, but only lawyer-linguists in the Court of Justice of the EU are responsible for translation (in their main language). The terminological analysis of the judgments in the field of EU Trade Mark translated into Slovene, shows how the terminology in those judgments has been developed and highlights the problems encountered by lawyer-linguists in translating them.